Accelerated weathering simulation on rheological properties and chemical structure of high viscosity modified asphalt: A temperature acceleration effect analysis. (25th January 2021) - Hu, Mingjun; Sun, Guoqiang; Sun, Daquan; Lu, Tong; Ma, Jianmin; Deng, Yue
Highlights: At 30 °C weathering aging temperature, the deteriorated rheological properties of HVMA are mainly due to solar radiation. At 50 °C weathering aging temperature, the thermal aging effect begins to appear under the stimulation of solar radiation. At 70 °C weathering aging temperature, HVMA has suffered a severe weathering coupling aging. The weathering aging rate of HVMA is fast initially and then slows down after 2 d aging. Abstract: High viscosity modified asphalt (HVMA) is widely used as the binder for permeable asphalt pavement. The service life of permeable asphalt pavement strongly depends on the weathering aging resistance of HVMA due to the large porosity of permeable asphalt pavement. In order to investigate the accelerated deterioration effect of temperature on the weathering aging process, a laboratory accelerated weathering aging tester was used to simulate the long-term weathering aging of HVMA at different aging temperatures (30 °C, 50 °C, and 70 °C) and different weathering aging days (0 12d). A series of rheological tests were conducted to study the influence of weathering aging temperature on the rheological properties of HVMA. Then, FTIR test was applied to characterize the changes in chemical composition of HVMA at different weathering aging temperatures. Furthermore, an aging kinetics model was put forward to further understand the effect of aging temperature on the weathering aging rate of HVMA. The results indicate that the weathering aging rate of HVMA is fast in the early aging stage (0 2d) and slows down in the later aging stage (2 12d). The increase of aging temperature has a significant accelerated deterioration effect on the chemo-rheological properties of HVMA during weathering aging process. At 30 °C aging temperature, the deteriorated rheological properties of HVMA are mainly due to the aging of solar radiation. As the aging temperature increases to 50 °C, the thermal aging effect of HVMA begins to appear under the stimulation of solar radiation. When the aging temperature rises to 70 °C, HVMA has suffered from a severe coupled aging of high temperature, solar radiation and humidity. This coupled aging effect leads to a significant asphalt oxidation and polymer degradation, which is the main reason for the severely deteriorated rheological properties of HVMA. The proposed aging kinetics model results also confirm the accelerated deterioration effect of temperature during weathering aging process.